Prostozidar na obisku pri geniju, prostozidarju brez predpasnika, ki je v mladosti živel tudi v Mariboru - Premzl, Primož (Časopis za zgodovino in narodopisje, 2025)
Nikola Tesla, one of the greatest geniuses, spent several months of his life in Maribor. Some of his biographers are convinced that this was a period of maturation that significantly influenced his later brilliant path as one of the greatest minds of humanity. According to the knowledge available to us, Tesla was not a Freemason; however, his well-known thoughts, which often appear in the media and on social networks, are similar to the principles and values upheld by Freemasonry. One of the few Slovenes who had personal contact with Nikola Tesla was Academician Dr. Milan Vidmar in New York in 1936. He described his meeting with Tesla in his book Between Europe and America, published in 1937. The account of the meeting made a strong impression on him, and therefore some of these reflections are also recorded in this contribution.
Keywords: biografije; biographies; freemasonry; inventors; izumitelji; Maribor; Milan Vidmar; Nikola Tesla; prostozidarstvo